(untitled) (Journal of Oriental Studies, 2020)
The article is devoted to the treatise of the Otrar thinker Abu Nasr al-Farabi “al-Mauyza” (Sermon), versions of which are preserved in the world archives under various names. In the history of science this work first appeared under the title “Kalam Abi Nasr al-Farabi fi Vasaya...” in the work ibn Masquih (929-1030) “al-Hikmatu-l halida”, in the early 17th century was named “Jawamiu-s siasati” in a work of bibliographic nature by Haji Khalifa (1609-1657) “Kashf al-zunun,” then based on the research of scientists who had taken up the systematic study of the works of the heritage of the thinker since the mid-20th century, put into scientific circulation under several titles the work from the written heritage of Abu Nasr al-Farabi unpublished version was discovered in the archive of the “Arab Institute of Manuscripts” in Cairo. In addition, the article states that there is a great opportunity to return to their homeland the written heritage of great scientists, valuable exhibits concerning the history of Central Asia and Kazakhstan, which are located in the funds and archives of libraries of foreign countries through comprehensive research carried out within the framework of state programs initiated by the First President of Kazakhstan: “Cultural heritage,” “People in the stream of history”, “Seven facets of the Great Step”. Key words: al-Farabi heritage, source, sources, manuscripts, research, introduction to scientific circulation.